Tumor mutation burden as a biomarker for lung cancer patients treated with pemetrexed and cisplatin (the JIPANG‐TR). Issue 1 (30th November 2020) - Sakai, Kazuko; Tsuboi, Masahiro; Kenmotsu, Hirotsugu; Yamanaka, Takeharu; Takahashi, Toshiaki; Goto, Koichi; Daga, Haruko; Ohira, Tatsuo; Ueno, Tsuyoshi; Aoki, Tadashi; Nakagawa, Kazuhiko; Yamazaki, Koji; et al.
Abstract: The JIPANG study is a randomized phase III study of pemetrexed/cisplatin (Pem/Cis) versus vinorelbine/cisplatin (Vnr/Cis) for completely resected stage II‐IIIA non‐squamous non‐small cell lung cancer (Ns‐NSCLC). This study did not meet the primary endpoint (recurrence‐free survival, RFS) but Pem/Cis had a similar efficacy to Vnr/Cis with a better tolerability. Tumor mutation burden (TMB) is thought to have a predictive value of immune checkpoint inhibitors. However, the relevance of TMB to cytotoxic chemotherapy remains unknown. This exploratory study investigates the relationship between tumor mutation profiles and clinical outcome of Pem/Cis. Formalin‐fixed, paraffin‐embedded tumor tissues (n = 389) were obtained from the patients. Mutation status of tissue DNA was analyzed by targeted deep sequencing. Epidermal growth factor receptor ( EGFR) mutations were detected frequently in Ns‐NSCLC (139/374). Patients without any EGFR mutations experienced longer RFS in the Pem/Cis arm versus Vnr/Cis arms. Pem/Cis in patients with high TMB (≥12‐16 mut/Mb) tended to have improved survival. In patients with wild‐type EGFR, TMB ≥ 12 mut/Mb was significantly associated with improved RFS with Pem/Cis versus Vnr/Cis (not reached vs 52.5 months; hazard ratio (HR) 0.477). It could be proposed that TMB was predictive of RFS benefit with Pem/Cis versus Vnr/Cis in Ns‐NSCLC. Further investigation is required to determine whether TMB combined with EGFR mutation status could be used as a predictive biomarker. Abstract : Tumor mutation burden (TMB) is a predictor of immune checkpoint inhibition therapy. When combined with EGFR mutation status, TMB could be a predictive biomarker of postoperative adjuvant chemotherapy with pemetrexed plus cisplatin for patients with non‐squamous non‐small cell lung cancer. Personalized adjuvant therapy will continue to advance.